2013
DOI: 10.1016/j.joca.2013.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with reduced work productivity among people with chronic knee pain

Abstract: This longitudinal study found that among this cohort of people with chronic knee pain, the burden of reduced work productivity is mainly attributable to presenteeism rather absenteeism. This study demonstrated that effective strategies to increase work productivity should focus on reducing knee pain or physical disability especially among workers in manual or semi-manual labour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…Our findings thus suggest that knee pain negatively impact on physical aspects of health-related QoL, in line with data from the OAI 19 and the Research on Osteoarthritis Against Disability Study. 3 …”
Section: Discussionmentioning
confidence: 99%
“…Our findings thus suggest that knee pain negatively impact on physical aspects of health-related QoL, in line with data from the OAI 19 and the Research on Osteoarthritis Against Disability Study. 3 …”
Section: Discussionmentioning
confidence: 99%
“…The most common joint disease, osteoarthritis (OA), leads to absenteeism at work due to disability associated with joint pain and dysfunction1. Risk factors including obesity, aging, trauma, and lipid metabolism are etiological factors in OA.…”
mentioning
confidence: 99%
“…However, a recent review8 found patients with hip or knee osteoarthritis were more likely to report reduced work capacity than the general population. A recent longitudinal study among people with chronic knee pain found that absenteeism was related to low psychological well-being, whereas presenteeism was associated with poor self-reported physical function and higher occupational physical demands 9. There has been a growing interest in conceptualising and adequately measuring the burden of reduced work productivity among people with painful knee osteoarthritis 10 11…”
mentioning
confidence: 99%